VHE Gamma-ray supernova remnants - Funk, Stefan (Advances in Space Research, 2008)
Increasing observational evidence gathered especially in X-rays and gamma-rays during the course of the last few years support the notion that Supernova remnants (SNRs) are Galactic particle accelerators up to energies close to the "knee" in the energy spectrum of Cosmic rays. This review summarises the current status of gamma-ray observations of SNRs. Shell-type as well as plerionic type SNRs are addressed and prospect for observations of these two source classes with the upcoming GLAST satellite in the energy regime above 100 MeV are given. (C) 2007 Published by Elsevier Ltd on behalf of COSPAR.
CRIS-Team WoS Importer:2020-01-15